ISLAMIC RELIGIOUS EDUCATION LEARNING STRATEGY TO REALIZE EIGHT STUDENT CHARACTERS IN STATE ELEMENTARY SCHOOL 107405 SEI ROTAN - Erna Wati (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to determine: (1) the program carried out in 107405 SeiRotan Public Elementary School in realizing eight student characters, (20plans carried out by Islamic Religious Education teachers in realizing eightstudent characters in 107405 Sei Rotan Public Elementary School, (3)strategy what can be done by Islamic Religious Education teachers inrealizing the eight characters of students, and (4) the implications arisingfrom the strategies carried out by Islamic Religious Education teachers onthe formation of student characters in practicing worship. The researchmethod uses qualitative research, namely research conducted naturally byutilizing researchers as research instruments. The subjects of this studywere Islamic Religious Education teachers, principals, and students. Dataretrieved through observation, documentation, and interviews. Data isanalyzed based on data reduction, data presentation, and drawingconclusions. The results of this research can be concluded as follows: (1)the program carried out by has accommodated the coaching of eightstudent characters (religious, honest, tolerance, hard work, creative,independent, democratic, and disciplined) through the 3 S program, duhaprayers, midday prayers, commemoration of Islamic holidays, flagceremonies, extracurricular activities (scouting, sports, and art), cleanFriday activities, gymnastics, OSN activities, (2) planning by teachers ofEducation Islamic religion in realizing the eight characters of students isdone by teachers by preparing learning plans based on the vision andmission of the school, competency standards, and also based oninteresting and innovative learning patterns, (3) strategies undertaken byIslamic Religious Education teachers in the development of eight studentcharacters implemented from the implementation of learning wasinteresting and fun shows an enthusiastic attitude towards learningcarried out by the teacher, and (4) the implication of coaching the eightcharacters of students is a positive change in the character of students andachievement of learning outcomes.